THE IMMUNE RESPONSE TO HUMAN IMMUNODEFICIENCY VIRUS - Nuriasti, Rovera; Putri, Dyah Arista; Aulia, Rashieka Salma (Fakultas Kedokteran Universitas Jenderal Soedirman, 2025)
Human Immunodeficiency Virus (HIV) is an infectious agent that disrupts the immune system by destroying CD4+ T lymphocytes, thereby triggering a decline in immune function and the development of Acquired Immunodeficiency Syndrome (AIDS). HIV employs a complex infection mechanism, including binding to host cell receptors, integration of genetic material, and modulation of the immune system to evade detection. The immune response to HIV involves the innate immune system, such as the activation of macrophages and dendritic cells through pattern recognition receptors, as well as the adaptive immune system through the activity of cytotoxic T cells and antibody production by B cells. However, HIV utilizes various strategies to evade immune responses, including rapid mutation and down-regulation of immune molecule expression. Antiretroviral therapy (ART) is the primary strategy for inhibiting HIV replication and maintaining immune system function, and it has been proven effective in reducing the morbidity and mortality associated with HIV infection, although a curative therapy has yet to be discovered.